Catherine ou le corps de la Passion - Aubin-Boltanski, Emma (France, 2011)
Native of the Lebanese mountains, housewife and mystic, Catherine pursues daily the project of being a saint. Every year, on Good Friday, she simultaneously revives Christ’s Passion and Mary’s suffering. As a living icon, she offers her own body to the sight and touch of hundreds of worshippers. She blurs the border of sacred and profane, female and male, parent and child, past and present, image and living person.
Center for Religious Studies, CEU
Duration: 00:57:00